WANPRESTASI PEMBELI TERHADAP PEMILIK TOKO SELEMPANGKU DALAM PERJANJIAN JUAL BELI BENDA BERGERAK DI KOTA PONTIANAK - NIM. A1011211276, DHEA APRIANTI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract A sales and purchase agreement is one of the most common forms of contractual obligations in economic activity. One implementation is the buy-sell system, widely used by small businesses, such as Toko Selempangku in Pontianak City. However, in practice, buyers often default on their obligations, either through late payments, unilateral cancellations, or rejection of ordered goods. These issues not only harm the seller but also create legal uncertainty in sales and purchase transactions. Based on this, this study focuses on examining the forms of buyer default against the owner of Toko Selempangku. Therefore, the author formulates the research problem as follows: